On Teaching Malware Analysis on Latest Windows (Journal of The Colloquium for Information Systems Security Education, 2022)
Microsoft Windows operating systems are the most popular desktop operating systems. 83% of malware attacks target Windows. Windows 10 has a market share of 78.45% out of all Windows versions on the market. However, we find security related courses are often taught on Linux or run on older Windows versions. In this paper, we present our practice of teaching malware analysis on the latest Windows (10). We are among the first using the latest Windows (10) for teaching malware analysis. We design the labs and assignments on the pre-configured Windows 10 VM supplemented by the Kali VM. A virtual Cyber Range is created for students to access the two VMs over a cloud. We present our curriculum and learning assessment scheme. Our practice has been validated through surveys on both face-to-face and online classes.
Keywords: malware analysis; Windows; VM; XCP-ng